Self-assembled innervated vasculature-on-a-chip to study nociception. (1st July 2023) - Kumar, Vardhman; Kingsley, David; Madhurakkat Perikamana, Sajeeshkumar; Mogha, Pankaj; Goodwin, C Rory; Varghese, Shyni
Abstract: Nociceptor sensory neurons play a key role in eliciting pain. An active crosstalk between nociceptor neurons and the vascular system at the molecular and cellular level is required to sense and respond to noxious stimuli. Besides nociception, interaction between nociceptor neurons and vasculature also contributes to neurogenesis and angiogenesis. In vitro models of innervated vasculature can greatly help delineate these roles while facilitating disease modeling and drug screening. Herein, we report the development of a microfluidic-assisted tissue model of nociception in the presence of microvasculature. The self-assembled innervated microvasculature was engineered using endothelial cells and primary dorsal root ganglion (DRG) neurons. The sensory neurons and the endothelial cells displayed distinct morphologies in presence of each other. The neurons exhibited an elevated response to capsaicin in the presence of vasculature. Concomitantly, increased transient receptor potential cation channel subfamily V member 1 (TRPV1) receptor expression was observed in the DRG neurons in presence of vascularization. Finally, we demonstrated the applicability of this platform for modeling nociception associated with tissue acidosis. While not demonstrated here, this platform could also serve as a tool to study pain resulting from vascular disorders while also paving the way towards the development of innervated microphysiological models.